Effect of industrial processing and storage procedures on oxysterols in milk and milk products. Issue 2 (4th January 2021) - Risso, D.; Leoni, V.; Fania, C.; Arveda, M.; Falchero, L.; Barattero, M.; Civra, A.; Lembo, D.; Poli, G.; Menta, R.
Abstract : Oxysterols are products of enzymatic and/or chemical cholesterol oxidation. Their measurement during and after a milk production chain could represent a useful tool to monitor and increase the commercial and nutritional value of milk. Abstract : Oxysterols are products of enzymatic and/or chemical cholesterol oxidation. While some of the former possess broad antiviral activities, the latter mostly originate from the deterioration of the nutritional value of foodstuff after exposure to heat, light, radiation and oxygen, raising questions about their potential health risks. We evaluated the presence of selected oxysterols in bovine colostrum and monitored the evolution of their cholesterol ratio throughout an entire industrial-scale milk production chain and after industrially employed storage procedures of milk powders. We report here for the first time the presence of high levels of the enzymatic oxysterol 27-hydroxycholesterol (27OHC) in concentrations of antiviral interest in bovine colostrum (87.04 ng mL −1 ) that decreased during the first postpartum days (56.35 ng mL −1 ). Of note, this oxysterol is also observed in milk and milk products and is not negatively affected by industrial processing or storage. We further highlight an exponential increase of the non-enzymatic oxysterols 7β-hydroxycholesterol (7βOHC) and 7-ketocholesterol (7KC) in both whole (WMPs) and skimmed milk powders (SMPs) during prolonged storage, confirming their role as reliable biomarkers of cholesterol oxidation over time: after 12 months, 7βOHC reached in both SMPs and WMPs amounts that have been found to be potentially toxic in vitro (265.46 ng g −1 and 569.83 ng g −1, respectively). Interestingly, industrial processes appeared to affect the generation of 7βOHC and 7KC differently, depending on the presence of fat in the product: while their ratios increased significantly after skimming and processing of skimmed milk and milk products, this was not observed after processing whole milk and milk cream.